Effect of Moisture Stress on Seed Germination of Spruce - Singh, Virendra; Paliwal, G. S. (Indian Forester, 1988)
The results of the experiment conducted to study the effect of different levels of moisture stress indicated that the germination of spruce seed decreased as the moisture stress increased. The seed germination was 0.25% only at a moisture stress of -7.0 atm. Even the slighest moisture stress of -0.5 atm tended to decrease the seed germination’ but the decrease in germination under the moisture stress of -O.5 atm was not significantly different from control.